Neurology at the Bedside - Kondziella, Daniel; Waldemar, Gunhild (Springer International Publishing : Imprint: Springer, 2017)
This updated and expanded new edition takes neurology trainees by the hand and guides them through the whole patient encounter - from an efficient neurological history and bedside examination through to differential diagnosis, diagnostic procedures and treatment. At each step the expert authors point out what is essential and what is not. Since the first edition, which was Highly Commended at the BMA Book Awards, chapters have been thoroughly revised and reflect the essential state-of-the-art knowledge neurologists need to acquire during their training. New graphic material has been added, as have new chapters including neurogenetics, neurorehabilitation, neurocritical care and heuristic neurological reasoning. In addition, this second edition now includes more than 100 unique case histories. Neurology at the Bedside, Second Edition is written for neurologists in all stages of training. Medical students, general practitioners and others with an interest in neurology will also find invaluable information here.
Keywords: Medicine.; Neurology.; elektronické knihy; electronic books